The Effects of Education and Telephone Nurse Follow-Up (Tele-Nursing) on Diabestes Management Self -Efficacy in Patients with Type 2 Diabetic Referred to Hamadans Diabetes Center in 2018 - Morteza Shamsizadeh; Soheila Shaadi; Younes Mohammadi; Seyed Reza Borzou (Hamadan University of Medical Sciences, 2021)
Objective: Diabetes is a common and costly disease. Nursing care services, not only are effective in reducing costs but also improve the quality of life and the relationship between the patient and the nurse. The aim of this research was evalution of telephone nursing Follow-up effects on self-efficacy in women with type 2 diabetes mellitus in Hamadan. Method: In this Clinical Trial study, 58 type 2 diabetic patients who met the inclusion criteria were recruited in Hamadan diabetes center by simple sampling. Patients were divided into two groups using block randomization. Data were collected using demographic and disease information questionnaire and Diabetes Management Self-Efficacy Scale (DMSES). Intervention in the experimental group was done by telephone nursing for 12 weeks in which phone calls were made during the first month (twice a week) and the second month (once a week). Phone nursing content included emphasis on diabetic diet, timely medication use, insulin injection, recreation and exercise, self care, stress management techniques, communication skills training, and more. The average duration of the call was 10-15 minutes on each call, and the time of phone call was agreed between 8 a.m. and 6 p.m. Patients were told that telephone nursing is free so patients could contact the researcher by phone or text if they had any questions. It should be noted that the patients in the control group received only the follow-up and routine care of the Hamadan diabetes center. Finally, the data were analyzed using IBM SPSS Statistics version 19 software. Results: Findings of the study showed that the mean of self-efficacy in both groups before intervention was not statistically significant (P=0.15). After training the intervention group, the mean self-efficacy at one and two months after treatment was significantly improved compared to the control group (P<0.001) Conclusion: According to the findings of this study, it can be concluded that nurse telephone follow-up was effective in promoting self-efficacy in patients with diabetes.